Effect of climate change on the potential distribution of Heloderma alvarezi (Squamata, Helodermatidae) - Aarón Gómez-Cruz (Pensoft Publishers, 2021)
Climate change represents a real threat to biodiversity conservation worldwide. Although the effects on several species of conservation priority are known, comprehensive information about the impact of climate change on reptile populations is lacking. In the present study, we analyze outcomes on the potential distribution of the black beaded lizard (Heloderma alvarezi Bogert & Martin del Campo, 1956) under global warming scenarios. Its potential distribution, at present and in projections for the years 2050 and 2070, under both optimistic and pessimistic climate change forecasts, were computed using current data records and seven bioclimatic variables. General results predict a shift in the future potential distribution of H. alvarezi due to temperature increase. The optimistic scenario (4.5 W/m2) for 2070 suggests an enlargement in the species’ distribution as a response to the availability of new areas of suitable habitat. On the contrary, the worst-case scenario (7 W/m2) shows a distribution decrease by 65%. Moreover, the range distribution of H. alvarezi is directly related to the human footprint, which consequently could magnify negative outcomes for this species. Our research elucidates the importance of conservation strategies to prevent the extinction of the black beaded lizard, especially considering that this species is highly threatened by aversive hunting.